Efficacy and Safety of Trametinib in Neurofibromatosis Type 1-Associated Plexiform Neurofibroma and Low-Grade Glioma: A Systematic Review and Meta-Analysis - Dun Wang; Lingling Ge; Zizhen Guo; Yuehua Li; Beiyao Zhu; Wei Wang; Chengjiang Wei; Qingfeng Li; Zhichao Wang (MDPI AG, 2022)
Trametinib has been used in neurofibromatosis type 1 (NF1) patients, especially those with unresectable nerve tumors, but no systematic review based on the latest studies has been published. We conducted this meta-analysis to evaluate the effectiveness and safety of trametinib in treating NF1-related nerve tumors. Original articles reporting the efficacy and safety of trametinib in NF1 patents were identified in PubMed, EMBASE, and Web of Science up to 1 June 2022. Using R software and the 'meta' package, the objective response rates (ORRs) and disease control rates (DCRs) were calculated to evaluate the efficacy, and the pooled proportion of adverse events (AEs) was calculated. The Grading of Recommendations, Assessment, Development and Evaluation system was used to assess the quality of evidence. Eight studies involving 92 patients were included, which had a very low to moderate quality of evidence. The pooled ORR was 45.3% (95% CI: 28.9-62.1%, I2 = 0%), and the DCR was 99.8% (95% CI: 95.5-100%, I2 = 0%). The most common AEs was paronychia, with a pooled rate of 60.7% (95% CI: 48.8-72.7%, I2 = 0%). Our results indicate the satisfactory ability to stabilize tumor progression but a more limited ability to shrink tumors of trametinib in NF1-related nerve tumors. The safety profile of trametinib is satisfactory.